PENDIDIKAN KESEHATAN PHBS SEBAGAI UPAYA PENCEGAHAN PENYAKIT TIDAK MENULAR PADA MASYARAKAT DESA PEDIWANG KECAMATAN KAO UTARA - Blandina, Olivia; Tjingaisa, Yurensi Felni (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Healthy clean living behavior is basically an effort to transmit experiences regarding healthy lifestyles through individuals, groups or the wider community using communication channels as a medium for sharing information. Healthy living is something that should be implemented by everyone, considering that the health benefits are so important for everyone. Creating a healthy life is actually very easy and cheap, compared to the costs we have to pay for treatment if we experience health problems. However, what happens is that most people have already contracted a new disease, so it will create losses for those who experience it. The community service carried out lasted for 1 day in the Pediwang Village community, Kao District, which aimed to prevent non-communicable diseases through health education about Clean and Healthy Living Behavior in Pediwang Village, North Kao District. This activity was carried out by lecturers and students of the Nursing Study Program, Hein Namotemo University. The method used is health education. The implementation stage begins with health education delivered by lecturers from the Nursing study program at Hein Namotemo University, which is followed by discussion and questions and answers. The results of health education show that the people of Pediwang Village, Kao District have increased their knowledge or are able to understand the meaning, causes, treatment and prevention of non-communicable diseases by practicing clean and healthy living behavior.